Molecular engineering of rhodanine dyes for highly efficient D-π-A organic sensitizer. (September 2018) - Li, Ranran; Xie, Liqing; Feng, Haijing; Liu, Bo
Abstract: Due to the strong electron-withdrawing capability, the rhodanine unit is widely used as the acceptor of the D-π-A organic sensitizer. However, in this unit, the carboxyl group is shut out from the whole conjugation system, which affects the injection of the excited electrons, leading to poor photovoltaic performance. Herein, with the introduction of cyanoacetic acid into the rhodanine segment, two novel indoline sensitizers, CS-22 andCS-24, based on D-π-A construction are designed and synthesized. With this modification, the carboxyl group is conjugated with the whole molecule, leading to sharp enhance of light-harvesting capability of the dye and more important, quite smooth electron injection process. Moreover, the introduced long alkyl chain can also prevent the π-aggregation on TiO2 surface and restrain the charge recombination effectively. Accordingly, using the modified acceptor, the photovoltaic performance is significantly improved: an extremly high PCE of 8.48% is obtained byCS-22 sensitized DSSC, which is the highest value among rhodanine dyes without any co-adsorbent. Our work demonstrates that the introduction of conjugated carboxyl group is greatly benefit for the improvement of rhodanine dyes in photovoltaic performance, providing a powerful strategy for the development of rhodanine based highly efficient D-π-A organic sensitizer in the future. Graphical abstract: The modified rhodanine acceptor with long alkyl chain is greatly favorable to efficient interfacial electron transfer, providing a powerful strategy for the development of rhodanine based highly efficient D-π-A organic sensitizer in the future. Highlights: To develop efficient sensitizer, the modified rhodanine acceptor is employed. The modified acceptor with alkyl chain is favorable to interfacial electron transfer. Without co-adsorbent, CS-22 shows the record PCE of 8.48% with long-term stability.